Avaliação de métodos para o estudo da resistência de genótipos de soja a Meloidogyne javanica (Treub) Chitwood - Bruinsma, Juliana Souza da Silva (2013)
Soybean is the most important oilseed crop grown in the world, though its production may be limited by various pathogens, among them stands out the gall nematode (Meloidogyne spp.). This study aimed to evaluate methods for the study of resistance of soybean genotypes to M. javanica in the field and in the greenhouse and select from among these, soybean genotypes with resistance and / or tolerance to nematode. To conduct the study, we employ twelve cultivars of soybean (CEPsRR 07224, CEPsRR 08414, CEPsBt 09018, CEPsBt 09021, CEPsBt 09030, CEPsBt 09033, CEPsBt 09036, CEPsBt 09049, CEPsRR 09086, CEPsBt 10129, FUNDACEP 58RR and FUNDACEP 64RR), beyond susceptible control (BRS 243RR) and control resistant (BRS 256RR). The field work was conducted in the area of natural occurrence of the nematode in the municipality of Julio de Castilhos, RS, in two sowing dates, where we evaluated the intensity of galls on the roots of soybean plants. In the greenhouse, the study was conducted in Cruz Alta, RS, where the plants were inoculated with inoculum from infected roots of the field, which remained for 55 days in a greenhouse until the evaluation, which assessed: number and index galls, number of egg mass, egg number and reproductive factor. In the field genotypes CEPsRR 07224, CEPsBt 09036 and CEPsBt 10129 had the lowest intensity of galls. Only genotype CEPsRR 07224 was classified as resistant, and the others classified as moderately resistant. In the greenhouse, the genotypes CEPsBt 09036 and CEPsBt 10129 had the lowest number of galls and gall index. Although all genotypes present FR> 1, had low values of number of eggs and reproduction factor, genotypes CEPsBt 09033, CEPsBt 09036 and CEPsBt 10129. However, using as criterion the gall index and FR, it was found that CEPsBt 09036 and CEPsBt 10129 behaved as tolerance under field conditions and greenhouse conditions.